Adverse events with COVID-19 vaccination (precaution dose) among the elderly population aged 60 years and above in South India - Ade, Anju Damu; Vallepalli, Chandrashekhar; Guthi, Visweswara Rao; Prathyusha, T. V. D.; Nagraj, K. (International Journal Of Community Medicine And Public Health, 2023)
Background: India started administering the precaution dose or the Booster dose of COVID vaccine from 10 January 2022 to comorbid people aged 60 and above. To identify the adverse events with COVID-19 vaccination (precaution dose) among the elderly population aged 60 years and above. To determine the association between adverse reactions and sociodemographic factors, morbidity profile and previous history of COVID 19. Methods: This cross-sectional study was undertaken at COVID- 19 vaccination centre, of SVIMS, Tirupati. AP from January 2022 to July 2022. Data was collected by interviewing the study subjects. Study respondents who received COVID-19 vaccine were observed for a period of 30 minutes and after 48 hours, study participants were contacted through telephone to find out any vaccine related adverse effects. Results: Overall, 676 of 60 years or older received their precaution dose. Majority of the respondents were in 60-70 years age group (60.8%) males (n=397, 58.7%) were higher than females (n=279,41.3%). Out of 676, 34 (5.0 %) participants reported adverse effects after 1st or 2nd dose. With regard to precaution dose, only 43 (6.4%) reported adverse events within the 30 minutes of receiving COVID-19 vaccine. While 54 (8.0%) reported adverse events in last 48 hours after receiving COVID-19 vaccine (precaution dose). Spectrum of symptoms reported were fever, anxiety, dizziness/giddiness, body pains, headache, nausea, pain at injection site, pain in abdomen, swelling at injection site, rash. Conclusions: Only 43 (6.4%) reported adverse events within the 30 minutes of receiving COVID-19 vaccine while 54 (8.0%) reported adverse events in last 48 hours after receiving COVID-19 vaccine(precaution dose).There were no reports of serious adverse effects.